ON THE OPTIMAL RECEIVER ACTIVATION FUNCTION FOR DISTANCE-BASED GEOGRAPHIC TRANSMISSIONS - RAO, MURALI; GOSWAMI, TATHAGATA D.; GLOVER, JOSEPH; SHEA, JOHN M. (SIAM journal on applied mathematics, 2011)
In wireless networks, the channels are often subject to random variations that limit the reliability of communications between any two radios. Geographic transmission strategies can improve the performance in such networks by allowing any of a transmitter's neighbors that successfully receive a transmission and are in the direction of the packet's destination to forward the packet to the destination. However, requiring all of the radios in a network to keep their receivers on to receive geographic transmissions will significantly shorten the network lifetime by depleting the energy of the radios in the network. In this work, we investigate an optimal strategy for deciding which neighbors of a transmitter should activate to try to recover a transmission. We find a solution to this problem by solving for a related measure in a constrained optimization problem. We present results that compare the performances of the optimal approach, our previous suboptimal efforts, and a conventional approach.